Prevalence and Characteristic of Swine-Origin mcr-1-Positive Escherichia coli in Northeastern China - Cheng, Ping; Yang, Yuqi; Cao, Sai; Liu, Haibin; Li, Xiaoting; Sun, Jichao; Li, Fulei; Ishfaq, Muhammad; Zhang, Xiuying (Frontiers in Microbiology, 2021)
The emergence of plasmid-mediated colistin resistance gene mcr-1, threatening the last-line role of colistin in human medicine. With mcr-1-positive Escherichia coli (E. coli) isolated from food animal has been frequently reported in China, the prevalence of mcr-1 in food animal has attracted public attention. In the present study, a total of 105 colistin-resistant E. coli strains were isolated from 200 fecal samples collected from 6 swine farms in northeastern of China. mcr-PCR revealed the prevalence of mcr-1 in colistin-resistant E. coli was 53.33 (56/105). The mcr-1-positive E. coli showed extensive antimicrobial resistance profiles with the presence of additional resistance genes, increased expression of multidrug efflux pumps-associated genes and increased biofilm formation ability. MLST differentiated the all mcr-1-positive E. coli into 25 STs and five unknown ST (untypable), the most common ST was ST10 (n = 11). By phylogenetic group classification, the distribution of all mcr-1-positive E. coli belonging to group A, B1, B2 and D was 46.43, 35.71, 5.36 and 5.36, respectively. Conjugation experiment demonstrated most of mcr-1 were transferable at the frequencies of 2.68 ´ 10-6 to 3.73 ´ 10-3 among 30 representative mcr-1-positive E. coli. The plasmid replicon types IncI2 (n =9 ), IncX4 (n = 5), IncHI2 (n = 3), IncN (n = 3), IncP (n = 1) were detected in the transconjugants. The results of growth assay, competition experiment and plasmid stability testing showed that acquisition of mcr-1-harboring plasmids could reduce fitness of bacterial hosts, but mcr-1 maintained stable in the recipient strain. Due to the potential possibility of these mcr-1-positive E. coli transmit to humans through food chain or horizontal transmission, therefore, it is necessary to continuously monitor the prevalence and dissemination of mcr-1 in food animal, particularly in swine.